Knockdown of an ATP-binding cassette transporter in resistant western corn rootworm larvae partially reverses resistance to eCry3.1Ab protein - Adriano E. Pereira; Kyle J. Paddock; Jacob A. Corcoran; Zixiao Zhao; Michelle L. J. Gregory; Thomas A. Coudron; Bruce E. Hibbard; Kent S. Shelby; Man P. Huynh (Scientific Reports)
Abstract The western corn rootworm (WCR), Diabrotica virgifera virgifera LeConte, has evolved resistance to nearly every management tactic utilized in the field. This study investigated the resistance mechanisms in a WCR strain resistant to the Bacillus thuringiensis (Bt) protein eCry3.1Ab using dsRNA to knockdown WCR midgut genes previously documented to be associated with the resistance. ATP-binding cassette transporter (ABCC4), aminopeptidase-N, cadherin, and cathepsin-B were previously found to be differentially expressed in eCry3.1Ab-resistant WCR larvae when compared to susceptible larvae after feeding on maize expressing eCry3.1Ab and its near-isoline. Here we compared the susceptibility of resistant and susceptible WCR larvae to eCry3.1Ab protein in presence or absence of dsRNA targeting the above genes using 10-day diet overlay toxicity assays. Combining ABCC4 dsRNA with eCry3.1Ab protein increased susceptibility to Bt protein in WCR-resistant larvae, but the other three genes had no such effect. Among 65 ABC transport genes identified, several were expressed differently in resistant or susceptible WCR larvae, fed on eCry3.1Ab-expressing maize versus its isoline, that may be involved in Bt resistance. Our findings provide strong evidence that ABCC4 is indirectly involved in WCR resistance to eCry3.1Ab protein by enhancing the effects of Bt-induced toxicity.